The Language Used in Advertisements for Herbal Medicines: A Case Study in Tehran, Iran - Hossein Salarian; Evan Afri (International Journal of English and Applied Linguistics (IJEAL), 2022)
Not only are quality and price important features for products, but environmental awareness or social commitment has a critical function in convincing target audiences in buying the products. Therefore, the present study takes into account the language used in the advertisements for herbal medicines in Tehran, Iran. The researcher considers critical discourse analysis (CDA) as the theoretical framework and empirical grounding for the advertisements of herbal medicines. To this end, using a qualitative approach, the data are collected from the words, phrases, clauses, and sentences of the advertisements through a questionnaire in which 45 participants were involved. The researcher used Fairclough’s (1992) three dimension framework for the investigation of the advertisements in the cases of textual features, discursive features, and social features. The investigation displays the results of the language used in the advertisement for this study. Findings from the study point to the fact that there is a close relationship between the advertisement discourse and the sale of these products. Considering the social practices, the language in the advertisement has control or power over people. Moreover, the advertisement, not the product per se is the selling point and has control or power over the target audience. The findings of this study can contribute in other areas and offer some implications in the research considering the discourse analysis of advertisements.